'The Conscience of the Community': the Au Vaine of Rarotonga. Issue 1 (2nd January 2020) - Cutting-Jones, Hannah
ABSTRACT: The Au Vaine ('several women' in Cook Islands Māori), grassroots women's committees, worked to promote agricultural efforts and food security in Rarotonga during the 1920s and 1930s. A unique organization, the Au Vaine actively encouraged the growing of commercial crops alongside subsistence plantings at a time when women were being pushed towards the home and hearth, and men pulled to wage labour jobs. These women illustrate the powerful and often unheard voices Pacific women retained throughout this period, as well as the critical role of food in Pacific history. In this article I examine the context within which the Au Vaine emerged, discuss what distinguished them from other women's committees in Polynesia, highlight their purpose and impact on Cook Islands foodways, and explore some of the reasons they declined by the 1940s.